Effects of feed pressure and retentate flow rate on the performance of locally developed polysulfone membrane oxygen enrichment system - Ismail, Ahmad Fauzi; Tan, Chin Yin; Chan, Fook Kiong (Penerbit UTM Press, 2001)
Oxygen enrichment from surrounding air by using membrane is gaining wide acceptance through out the world today as an alternative to the conventional methods such as pressure swing adsorption and cryogenic system. Air separation using membrane is a more flexible process that requires lower capital investment and simple operation. Studies and testing had been performed on a locally new developed polysulfone hollow fiber membrane system, where effects of feed pressure and retentate flow rate on the oxygen enrichment were observed. At constant retentate flow rate, permeate enrichment increased and then decreased with pressure due to the effect of pressure difference across the membrane, which affects the permeability of the skin layer. While at constant pressure, the highest permeate enrichment value was obtained at highest retentate flow rate due to the increase of permeation resistance. The highest oxygen purity obtained in this experiment was 27.2% and the O2 permeate enrichment was 1.295.